ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL SASTRA INDONESIA: KAJIAN LITERATUR UNTUK RELEVANSI PENDIDIKAN KARAKTER - Tiara Brilliant; Bambang Riadi; Rahmat Prayogi (LPPM Universitas Bina Bangsa, 2024)
This research aims to identify educational values characters in Indonesian literary novels and analyzing their relevance towards character learning in schools. This research uses the method qualitative descriptive based on literature review, with a focus on six novels: Perahu Paper, Hayya, Dahlan Shoes, 9 Suns, Amelia, and Mata and Sea Man. The analysis results show that these novels contain various values characters such as honesty, hard work, responsibility, love of the country, caring environment, and democracy. These values ​​are aligned with the guidelines Ministry of National Education character education and relevant to be integrated in school curriculum. However, implementation in schools still faces challenges, especially in terms of teacher training and development of literature-based teaching materials. Therefore, a more integrative curriculum strategy is needed increasing teacher capacity to utilize novels as media character education learning. This research makes a contribution in optimizing the role of literary works in the formation of a moral generation of the nation and virtuous